2022
DOI: 10.1155/2022/9299397
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Autotransplantation and Orthotopic Kidney Transplantation: Two Different Approaches for Complex Cases

Abstract: Introduction. Transplantation surgery teams often have to face complex cases. In certain circumstances, such as occlusion of the iliac vessels or prior pelvic surgery, heterotopic kidney transplantation may not be feasible and orthotopic kidney transplantation (OKT) could be a good alternative. Kidney autotransplantation (KAT) has been described as a potential treatment for complex renovascular, ureteral, or neoplastic conditions. There are scarce data regarding the complications and outcomes of these procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Further, a total of 90 articles were excluded as per the study policy, and only 10 studies met the inclusion criteria (Figure 1). Full‐text reviews were performed on ten articles comprising 269 patients for this narrative review 1,2,5–12 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further, a total of 90 articles were excluded as per the study policy, and only 10 studies met the inclusion criteria (Figure 1). Full‐text reviews were performed on ten articles comprising 269 patients for this narrative review 1,2,5–12 …”
Section: Resultsmentioning
confidence: 99%
“…However, this review should be criticized for not specifying how many years the overall patient and graft survival rates have been. Further, this systematic review included only four papers published before 2014 whereas five more recent articles published in 2016 and later were added to our narrative review, 1,7–9 and similar survival rates at the postoperative 1st year were observed when compared to the previous studies 2,11 …”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Extensive ureteral stricture disease is often a sequela of inflammatory disorders like Crohn's disease, ureteral trauma, and iatrogenic injury [20,[47][48][49][50][51]. The 2022 European Association of Urology Guidelines on Urological Trauma state that RA is an alternative in patients with extensive ureteral loss, multiple attempts at ureteral repair, or who would not be candidates for other forms of ureteral reconstruction (Fig.…”
Section: Ureteral Trauma and Stricturesmentioning
confidence: 99%